English result : pre-intermediate. Student's book. - Paul Hancock; Annie McDonald; Annie McDonald (Oxford : Oxford University Press, 2012)
A new course with a strong focus on student motivation and communicative outcomes. The package includes DVDs and interactive whiteboard resources.
How to talk about names - How to ask for tourist - ow to talk about likes and dislikes - How to ask for things in a hotel - How to talk about - How to talk on the - How to have a conversation about work - How to apologize and respond to apologies - How to talk about food - How to ask and say where places are - How to describe - How to ask people to do things
Incluye contents.
Keywords: English language -- Textbooks for foreign speakers; English language -- Spoken English; English language